Profile of Blood Glucose and Insulin after Vitamin C and Vitamin E Supplementation on Active Teenagers - Irwadi, Irfiansyah; Kinandita, Hayuris; Mahmud, Jamaluddin; Herawati, Lilik (International Journal of Engineering and Technology, 2018)
Aim: Antioxidants, such as vitamin C and vitamin E, is widely used as supplements. The aim of this study is to analyze the profile of blood glucose, serum insulin, and  HOMA in active teenagers after vitamin C and vitamin E supplementation.Methods: Subjects (14-16 y.o) consisted of 12 boys and 5 girls, divided into 3 groups: control (4 boys, 2 girls), ‘moderate dose’ of vitamin C and vitamin E combination group (5 boys, 1 girls), and ‘high dose’ of vitamin C and vitamin E combination group (3 boys, 2 girls). The treatment was given for 5 days. Vitamin C and vitamin E for ‘moderate dose’ was 500mg;  200IU, and for ‘high dose’ was 1000mg; 400IU. Fasting Blood Glucose (FGB) and 1 hour BG (1hr_BG), fasting serum insulin (FSI) and 1 hour SI (1hr_SI) was collected after treatment. We also calculated the HOMA-IR and HOMA-β.Result: There was no significant difference on FBG, 1hr_BG, FSI, 1hr_SI, HOMA-IR, and HOMA-β (p≥ 0.05). However, mean FBG and 1hr_BG tended to be higher on the treatment groups. The control group had the lowest HOMA-IR and the highest HOMA-β.Conclusions: We suggest that the supplementation of vitamin C and vitamin E in active teenagers is not essential on glucose homeostasis.